2019
DOI: 10.1680/jener.19.00006
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the esterification of unsaturated free fatty acids

Abstract: The kinetics and thermodynamics of the esterification of oleic, linoleic and linolenic acids using a batch reactor are described in this study. The effect of relevant factors on ester conversion, such as reaction temperature, dose of sulfuric acid as a catalyst and methanol/free fatty acids (FFAs) (oleic, linoleic and linolenic acid) mole ratios are studied. The results show that the maximum conversion of oleic and linoleic acids was 88% at 40:1 methanol/FFAs molar ratio, temperature of 68°C, catalyst 2 wt% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Figure 6 shows that the catalyst was active for all those fatty acids, but higher conversion was reached with unsaturated ones (oleic acid > linoleic acid > stearic acid). A similar behavior has indeed been reported by other authors in the literature [51][52][53]. This trend may be ascribed to the polarity of the double bonds in the carbon chain leading to a higher reactivity of the carboxylic acid group [53][54][55].…”
Section: Catalyst Performancesupporting
confidence: 88%
“…Figure 6 shows that the catalyst was active for all those fatty acids, but higher conversion was reached with unsaturated ones (oleic acid > linoleic acid > stearic acid). A similar behavior has indeed been reported by other authors in the literature [51][52][53]. This trend may be ascribed to the polarity of the double bonds in the carbon chain leading to a higher reactivity of the carboxylic acid group [53][54][55].…”
Section: Catalyst Performancesupporting
confidence: 88%
“…The reaction has been carried out with different quantities of water like 2.0, 3.0, and 4.0 mL with keeping constant ration of oleic acid to methanol (1:29) at 70°C under reaction conditions. The conversions obtained as 14%, 8%, and 0.5%, respectively, indicate that water inhibited the rate of reaction 34–36 . This is due to blockage of active sites of catalyst, and hence, it could hinder diffusion of reactant and product from the surface.…”
Section: Resultsmentioning
confidence: 95%
“…The conversions obtained as 14%, 8%, and 0.5%, respectively, indicate that water inhibited the rate of reaction. [34][35][36] This is due to blockage of active sites of catalyst, and hence, it could hinder diffusion of reactant and product from the surface. The equilibrium of the reaction is affected due to the formation of water, and hence, reversible reaction occurs.…”
Section: Catalytic Applicationmentioning
confidence: 99%
“…However, they proposed an irreversible first-order kinetic model. Recently, Hawash et al (2019) also suggested irreversible first-order kinetic models for the esterification of linolenic, linoleic, and oleic acids with methanol and sulfuric acid at 2 wt% as the catalyst. The activation energies found were 3.19, 10.37, and 10.88 kcal/mol, respectively, proving that FFA composition also affects esterification kinetics.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…However, the catalyst concentration effect was also not explicit in none of them. Among other studies focused on kinetic models of FFA esterification to produce biodiesel, those reported by Sendzikiene et al (2004) and Hawash et al (2019) deserve to be mentioned. However, both studies proposed irreversible first-order kinetic models.…”
Section: Introductionmentioning
confidence: 99%